USULAN PENJADWALAN PREVENTIVE MAINTENANCE PADA MESIN OVERHEAD CRANE DENGAN MENGGUNAKAN METODE KEANDALAN DAN FMEA DI PT KORINDO HEAVY INDUSTRY - Gandara, Ganjar Sidik; Jantra, Noer Eden Ali; Sukandar, Rani Septiani (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT Korindo Heavy Industry is a company engaged in construction and heavy equipment, the company's production consists of various steel structures, pipe spools and special vehicles. The problem that occurs in the company is the buildup of material in the production process caused by the overhead crane machine as material handling being unable to transport material so that production activities at work stations are hampered. The purpose of this study was to determine the critical components of overhead cranes that contribute to high downtime and to determine machine performance including reliability, availability and maintainability. In addition, the research will also propose optimal maintenance actions. This study uses the Failure Mode and Effects Analysis method to identify failure modes and Reliability Availability Maintainability (RAM) to predict the reliability, availability and maintainability performance of a system or component. The results of the data processing that has been carried out obtained the highest criticality category based on the RPN, namely, absorber power trip (160), gearbox (120), cable (105), and lining brake (105), with a weibull distribution. The absorber power trip component is the smallest MTTF and MTTR values, namely 239.8078 hours and 0.9953 hours. Each critical component has an optimal operating time of 24 hours, except for the lining brake, which is 168 hours. the minimum time for each component to reach its initial condition with a maintainability value of 100% is 28 hours. the results of the availability calculation obtained the lowest component, namely, the gearbox component with an inherent availability value of 76.82% and 72% operational availability. Based on key performance indicators and company targets, the gearbox component availability value as a leading indicator has not yet reached the target. The conclusion of the research is to obtain more optimal maintenance action proposals for the four critical components of the BU-1 overhead crane, especially the gearbox components which have not reached the target